A comparison of running and contact loads in U18 and U20 international rugby union competition - Peeters, Alexis; Piscione, Julien; Lacome, Mathieu; Carling, Christopher; Babault, Nicolas (Biology of Sport, 2023)
The purpose of the present study was to characterize and compare locomotor and contact loads in U18 and U20 international rugby union competition during matches, and specifically during peak match-play phases using short rolling epochs and continuous ball-in-play (BIP) sequences. 20 international matches from French national teams were analysed in the U18 and U20 Six Nations Tournament respectively and World Rugby U20 Championship. Running loads were quantified using global positioning devices (16 Hz) and contact loads via video match analysis software. Players were split into forward (U18, n = 29; U20, n = 32) and back positional groups (U18, n = 20; U20, n = 24). Compared with U20 peers, U18 players covered a higher total distance (effect size (ES) = -0.76 ± 0.25) and at high-speeds per minute (> 4 m · s -1 ; ES = -0.55 ± 0.25) and performed more accelerations (ES = -0.71 ± 0.25). While a greater frequency of BIP sequences > 90 s duration was observed in U20s versus U18s match-play, U18s covered more total distance and high-speed distance (ES = -0.42 ± 0.13 and -0.33 ± 0.13 respectively) per minute during these longer sequences. During peak rolling phases shorter than 4 minutes, no clear differences existed between age categories in running activity, while U20 forwards performed more contact actions than U18 peers. The match-play loads observed in the present international U18 players suggest that they are ready to respond to the overall and peak demands observed in U20 competition. Moreover, the present information on peak activity phases can aid design of overload high-intensity conditioning sessions to respond to the running- and contact-demands identified in those competitions.